2015
DOI: 10.1037/adb0000098
|View full text |Cite
|
Sign up to set email alerts
|

Testing an expanded theory of planned behavior model to explain marijuana use among emerging adults in a promarijuana community.

Abstract: Opinions about marijuana use within the US are becoming increasingly favorable, making it important to understand how psychosocial influences impact individuals’ use within this context. Here we use the Theory of Planned Behavior (TPB) to examine the influence of initial attitudes, norms, and efficacy to resist use on initial intentions, and then the effect of initial intentions on actual marijuana use measured one year later using data drawn from a community with relatively high use. We expanded the tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…It follows that the individuals who had self-admitted themselves to a daycare center for substance use disorders to treat marijuana use should be instructed and reinforced in building-up strategies to resist marijuana use. Such strategies should include information about the negative long-term effects of marijuana [2,6,[12][13][14]33,[40][41][42], along with an explanation of the concept of self-control. Following cognitive-behavioral concepts [43], self-control is considered a specific behavior in a specific context which contains conflicting short-term and long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows that the individuals who had self-admitted themselves to a daycare center for substance use disorders to treat marijuana use should be instructed and reinforced in building-up strategies to resist marijuana use. Such strategies should include information about the negative long-term effects of marijuana [2,6,[12][13][14]33,[40][41][42], along with an explanation of the concept of self-control. Following cognitive-behavioral concepts [43], self-control is considered a specific behavior in a specific context which contains conflicting short-term and long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, in the present study we applied the Theory of Planned Behavior (TPB) [29,30] for the following reasons. Firstly, this theory has already been successfully used to identify predictors of marijuana use among adolescents and young adults (see [31][32][33]). This theoretical model has thus proved to be applicable in explaining marijuana use on the behavioral level and in supporting specific psychotherapeutic interventions.…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…Previous studies showed that the Theory of Planned Behaviour (TPB) can be useful in predicting intention and cannabis use (Malmberg et al, 2011;Ito, Henry, Cordova & Bryan, 2015). Intention is described as the strongest predictor of behaviour (Ajzen, 1985).…”
Section: Psychosocial Determinants Of Cannabis Use Among Adolescentsmentioning
confidence: 99%
“…One of the most common and highly cited is the Theory of Planned Behaviour, which has been supported in many studies through a wide spectrum of experimental applications including the prediction of behaviours related to drug usage 27 , gambling 28 , and sexual behaviours 29 . However, it is in the domain of physical activity that the model has been extensively applied 30,31 .…”
Section: Theory Of Planned Behaviour (Tpb)mentioning
confidence: 99%